Self-Efficacy as a Mediator of the Relationship Between Authoritative Parenting and Resilience Among Migrant Students in Semarang City - Alaiyya Rachma Gani; Dyah Ayu Rahmawati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Migrant university students constitute a unique group. Previous studies have examined the role of self-efficacy in resilience; however, these have generally been limited to academic contexts and adolescent populations. This study extends prior findings by examining an understudied population, namely, migrant university students who experience dual transitions (geographical and developmental). Therefore, this study aims to analyze the effect of authoritative parenting on resilience with self-efficacy as a mediator among migrant university students in Semarang City.This study employed a quantitative cross-sectional design with 246 participants selected through purposive sampling. Data were collected using the PSDQ, CD-RISC, and the General Self-Efficacy Scale, and were analyzed using PLS-SEM. The results indicate that authoritative parenting has a significant effect on resilience (β = 0.222; p < 0.001) and self-efficacy (β = 0.393; p < 0.001), and that self-efficacy significantly affects resilience (β = 0.474; p < 0.001). Self-efficacy mediates this relationship (β = 0.186; p < 0.001), accounting for 35.7% of the variance in resilience. These findings extend the resilience literature and practically support the development of university counseling services through a “Self-Efficacy Enhancement Based on Self-Actualization” program and seminars on “Building Self-Efficacy through Authoritative Parenting” for parents. Future research is recommended to employ qualitative approaches to further explore other factors not examined in this study. Keywords: authoritative parenting, migrant students, resilience, self-efficacy